2005
DOI: 10.1164/rccm.200406-746oc
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Kinetics as a Prognostic Marker of Ventilator-associated Pneumonia

Abstract: We investigated the value of procalcitonin kinetics as a prognostic marker during ventilator-associated pneumonia (VAP). This prospective, observational study was conducted in a medical intensive care unit in a university hospital. All consecutive patients with microbiologically proven VAP who survived 3 days after its diagnosis were included and grouped according to clinical outcome: favorable or unfavorable, defined as death, VAP recurrence, or extrapulmonary infection requiring antibiotics before Day 28. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
143
6
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(171 citation statements)
references
References 35 publications
10
143
6
12
Order By: Relevance
“…Multivariate analyses retained serum procalcitonin levels on days 1, 3, and 7 as strong predictors of unfavorable outcome. Based on these data, the author concluded that procalcitonin could be a prognostic marker of outcome during ventilator-associated pneumonia [14].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses retained serum procalcitonin levels on days 1, 3, and 7 as strong predictors of unfavorable outcome. Based on these data, the author concluded that procalcitonin could be a prognostic marker of outcome during ventilator-associated pneumonia [14].…”
Section: Discussionmentioning
confidence: 99%
“…At that concentration, sensitivity and specificity for not surviving VAP were 0.74 and 0.75, respectively. Luyt et al 19 measured procalcitonin levels on days 1, 3, and 7 after VAP occurrence and found that serum levels of procalcitonin were significantly higher in VAP patients who survived than in VAP patients who died. These authors identified the 7-day concentration (>0.5 ng/mL) as the cutoff point and stated that procalcitonin was an ideal independent indicator, with a more ideal sensitivity and specificity than those of WBC count and serum levels of C-reactive protein.…”
Section: Figurementioning
confidence: 99%
“…Clinically, the procalcitonin test is now widely used as a related biomarker indicative of infection, including the severity and prognosis of the infection. [15][16][17][18] The results of some studies [19][20][21] have suggested that the procalcitonin level might be relevant to the occurrence of VAP. In recent years, the Clinical Pulmonary Infection Score (CPIS) has been used both for the early diagnosis 22 of VAP and as a clinical indicator of the outcome of the infection.…”
mentioning
confidence: 99%
“…(40) Outros autores relataram que a persistência de níveis elevados de PCT apresenta valor preditivo de evolução desfavorável. (41) Entretanto, o impacto do uso deste marcador necessita ser investigado em outros centros, e em estudos com número maior de pacientes, antes da sua aplicação rotineira na prática clinica.…”
Section: Marcadores Biológicos De Infecçãounclassified